2019
DOI: 10.1038/s41467-019-10200-5
|View full text |Cite
|
Sign up to set email alerts
|

Ciclopirox inhibits Hepatitis B Virus secretion by blocking capsid assembly

Abstract: Chronic hepatitis B virus (HBV) infection can cause cirrhosis and hepatocellular carcinoma and is therefore a serious public health problem. Infected patients are currently treated with nucleoside/nucleotide analogs and interferon α, but this approach is not curative. Here, we screen 978 FDA-approved compounds for their ability to inhibit HBV replication in HBV-expressing HepG2.2.15 cells. We find that ciclopirox, a synthetic antifungal agent, strongly inhibits HBV replication in cells and in mice by blocking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…e grid map of various atoms of the ligands and receptor was generated by AutoGrid. It was previously reported that His51, Asp75, and Ser135 play an important role in the functioning activity of NS2B-NS3 protease [20,21]; thus, in the docking procedure, the grid box was chosen such that it incorporates these key residues. e energy scoring grid was prepared in x × y × z directions (80 × 80 × 80) with a grid spacing of 0.375Å.…”
Section: Ligands and Receptormentioning
confidence: 99%
“…e grid map of various atoms of the ligands and receptor was generated by AutoGrid. It was previously reported that His51, Asp75, and Ser135 play an important role in the functioning activity of NS2B-NS3 protease [20,21]; thus, in the docking procedure, the grid box was chosen such that it incorporates these key residues. e energy scoring grid was prepared in x × y × z directions (80 × 80 × 80) with a grid spacing of 0.375Å.…”
Section: Ligands and Receptormentioning
confidence: 99%
“…6-Cyclohexyl-1-hydroxy-4-methyl-2(1H)-pyridone (ciclopirox or CPX) and specifically it's olamine salt 6-Cyclohexyl-1-hydroxy-4-methyl-2(1H)-pyridone 2-aminoethanol salt (ciclopirox olamine or CPX-O) are antifungal, topical agents used in a variety of formulations such as gels, creams, shampoos for treatment of cutaneous fungal infections (19). However, over the last decade, the wide use of CPX or CPX-O in other diseases has been recognized (20)(21)(22). Furthermore, the safe therapeutic response of CPX-O has been tested in various animals including pigs and dogs (20).…”
Section: Introductionmentioning
confidence: 99%
“…Ciclopirox synergizes with entecavir (a deoxyguanosine analog) and tenofovir (a nucleotide analog reverse transcriptase inhibitor) and could become an important addition to orally active drug cocktails that actually eradicate the infection. For the peer review companion article, see Kang et al 23…”
Section: A Common Antifungal Might Eradicate Hepatitis B Virus Infectionmentioning
confidence: 99%